Inhaled Tobramycin in the Treatment of Severe Nosocomial Pneumonias - V. V. Moroz; A. N. Kuzovlev; S. G. Polovnikov; V. V. Stets; V. V. Varvarin (Общая реаниматология)
Objective: to evaluate the efficiency of using inhaled tobramycin in addition to systemic antibacterial therapy in the treatment of severe nosocomial pneumonias (NP) in critically ill patients. NP remains one of the most urgent problems in resuscitative units. Traditional intravenous injection of broad-spectrum antibiotics does not allow their bactericidal concentration to be achieved in the lung. Inhaled antibiotics in addition to systemic antibacterial therapy reduce the clinical symptoms of NP, assist the switching of patients to spontaneous breathing, and decrease the titer of microbes in bronchial lavage fluid. Subject and methods. This paper describes the experience of successfully using inhaled tobramycin during systemic antibiotic therapy in 10 patients with severe NP. Results. The use of inhaled tobramycin in addition to systemic antibiotic therapy is accompanied by a reduction in the signs of endogenous intoxication and acute respiratory failure, by a decrease in the titer of pathogenic microorganisms in bronchial alveolar fluid, and by an increase in their response to systemic antibiotics, by positive X-ray changes in 60% of the patients, and by the switch of 30% of the patients to spontaneous breathing. Adverse reactions as oto- and vestibu-lotoxicity were recorded in two patients; there were no cases of nephrotoxicity. Conclusion. The administration of inhaled tobramycin in a dose of 300 mg twice daily is effective and safe as a supplement to systemic antibiotic therapy in the treatment of severe NP caused by polyresistant gram-negative pathogens. Key words: nosocomial pneumonia, inhaled tobramycin.